Se Son Rose Fioriranno Uno Strano Caso di Nefrolitiasi - Marco Lombardi; Matteo Zoppi; Piero Bruschi; Federico Selvi; Maria Adele Signorini; Roberto Fanelli; Stefano Michelassi (AboutScience Srl, 2017)
Abstract non disponibile (narrative nephrology)